Organoleptic Characteristics of Catfish (Clarias batrachus) Sausages with the Addition of Chicken Eggshell (Gallus gallus domesticus) Powder - Haqi Miftah Fadilah; Ika Dyah Kumalasari (Universitas Darussalam Gontor, 2026)
Catfish (Clarias batrachus) sausage is a fish-based processed product with potential to be developed as a value-added and calcium-fortified food. Chicken eggshell (Gallus gallus domesticus) powder is a poultry by-product with high calcium content that can be utilized as an alternative calcium source. However, its incorporation may affect the sensory quality of food products; therefore, organoleptic evaluation is required to determine consumer acceptance. This study aimed to evaluate the effect of eggshell powder addition on the organoleptic characteristics of catfish sausage and to determine the most acceptable formulation. A Completely Randomized Design (CRD) with a single factor, namely the level of eggshell powder addition, was applied with four formulations: F0 (0%), F1 (10%), F2 (20%), and F3 (30%). Organoleptic evaluation was conducted using hedonic and descriptive tests involving 30 untrained panelists. The parameters assessed included color, smell, texture, taste, aftertaste, and overall acceptability. Data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test at a 95% confidence level. The results showed that increasing levels of eggshell powder significantly decreased sensory preference scores (p < 0.05), particularly for texture, taste, and aftertaste, due to the development of a gritty mouthfeel. Among the fortified formulations, F1 showed the most favorable balance between sensory acceptability and calcium enrichment with an overall hedonic score of 3.80 ± 0.76, while F0 had the highest overall sensory score (4.30 ± 0.59). In conclusion, the addition of 10% eggshell powder (F1) is recommended as the optimal formulation for producing calcium-fortified catfish sausage with acceptable sensory quality. The use of eggshell powder also offers a sustainable and cost-effective calcium source, supporting the valorization of poultry waste into functional food products.